2004
DOI: 10.1038/sj.bjc.6601704
|View full text |Cite
|
Sign up to set email alerts
|

Grade of recurrent in situ and invasive carcinoma following treatment of pure ductal carcinoma in situ of the breast

Abstract: The grade of recurrent in situ and invasive carcinoma occurring after treatment of pure ductal carcinoma in situ (DCIS) has been compared with the grade of the original DCIS in 122 patients from four different centres (The Royal Marsden Hospitals, London and Sutton, 57 patients; Guy's Hospital, London, 19 patients; Nottingham City Hospital, 31 patients and The Royal Liverpool Hospital, 15 patients). The recurrent carcinoma was pure DCIS in 70 women (57%) and in 52 women (43%) invasive carcinoma was present, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 32 publications
1
6
0
1
Order By: Relevance
“…Molecular phenotypes are of particular clinical significance if they outperform traditional histopathological parameters. Consistent with our previous findings, and that of others (Bijker et al, 2001;Kerlikowske et al, 2003;Millis et al, 2004;Silverstein et al, 1995) high nuclear grade predicts risk for a subsequent tumor event in a significant manner (HR 5.6, 95% CI 1.2 to 25.5). Although nuclear grade statistically stratifies a subpopulation of women with increased risk for a subsequent tumor event in this pilot set, roughly one third of women with high nuclear grade DCIS do not develop subsequent disease; while roughly one quarter of women with low grade DCIS develop subsequent disease.…”
Section: Relationship Between the Basal-like Subtype In Dcis And Nuclsupporting
confidence: 93%
See 1 more Smart Citation
“…Molecular phenotypes are of particular clinical significance if they outperform traditional histopathological parameters. Consistent with our previous findings, and that of others (Bijker et al, 2001;Kerlikowske et al, 2003;Millis et al, 2004;Silverstein et al, 1995) high nuclear grade predicts risk for a subsequent tumor event in a significant manner (HR 5.6, 95% CI 1.2 to 25.5). Although nuclear grade statistically stratifies a subpopulation of women with increased risk for a subsequent tumor event in this pilot set, roughly one third of women with high nuclear grade DCIS do not develop subsequent disease; while roughly one quarter of women with low grade DCIS develop subsequent disease.…”
Section: Relationship Between the Basal-like Subtype In Dcis And Nuclsupporting
confidence: 93%
“…Previous reports have demonstrated that ipsilateral tumors that develop subsequent to DCIS share many histological and genetic alterations with the primary lesion suggesting a clonal relationship (Bijker et al, 2001;Lininger et al, 1998;Millis et al, 2004;Waldman et al, 2000). Therefore, one might anticipate that high p16/high Ki67 in the initial DCIS lesion would characterize the subsequent invasive carcinoma.…”
Section: High P16 Mrna Levels Defines the Basal-like Subtype Of Invasmentioning
confidence: 97%
“…There is a correlation between the grade of DCIS and that of invasive carcinomas (3,4) and even with the grade of recurrent carcinoma and subsequent metastatic disease (5,6). Studies suggest that low-and high-grade DCIS evolve by means of distinct evolutionary pathways and that they show differences BREAST IMAGING: Detection Rates of Ductal Carcinoma in Situ with Biennial Digital Mammography Weigel et al (computed radiography and direct radiography technology) and conformed to national screening guidelines; none used digital breast tomosynthesis.…”
Section: Methodsmentioning
confidence: 99%
“…However, there are few scientific data regarding the accuracy of MRI as compared to mammography for evaluating DCIS (17). Previous studies showed variable sensitivities of breast CE‐MRI in detecting DCIS, ranging from 40% to 100% depending on the criteria used to define malignancy and the MRI features that were assessed (17–25). DCIS encompasses a histologically heterogeneous group of tumors that differ in growth patterns, cytologic features, and clinical behavior (1).…”
mentioning
confidence: 99%